2013
DOI: 10.1038/cddis.2013.173
|View full text |Cite
|
Sign up to set email alerts
|

Concentrative nucleoside transporter 1 (hCNT1) promotes phenotypic changes relevant to tumor biology in a translocation-independent manner

Abstract: Nucleoside transporters (NTs) mediate the uptake of nucleosides and nucleobases across the plasma membrane, mostly for salvage purposes. The canonical NTs belong to two gene families, SLC29 and SLC28. The former encode equilibrative nucleoside transporter proteins (ENTs), which mediate the facilitative diffusion of natural nucleosides with broad selectivity, whereas the latter encode concentrative nucleoside transporters (CNTs), which are sodium-coupled and show high affinity for substrates with variable selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Raw data were filtered and adapters were removed. Sequencing results demonstrated that the target sequence was 4.5x10 12 base pairs, with coverage of >99% and the sequencing depth of x250. A quality check was automatically performed on the raw data by the R 3.3.2 rCGH package, and the qualified data were used for subsequent analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data were filtered and adapters were removed. Sequencing results demonstrated that the target sequence was 4.5x10 12 base pairs, with coverage of >99% and the sequencing depth of x250. A quality check was automatically performed on the raw data by the R 3.3.2 rCGH package, and the qualified data were used for subsequent analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple chromosome sites with copy number variation (CNV) in CIN-type colorectal cancer (11). If CNV occurs inside or around the tumor-associated gene sequences, oncogenes may be activated and anti-oncogenes may be inactivated, which eventually induces tumorigenesis (12). A previous study indicated that increased CNVs may be associated with the progression of colitis gravis to colorectal cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive in vitro evidence supports the view that hENT1 activity is a key determinant of gemcitabine action. Overexpression of hENT1 enhances gemcitabine response in human pancreatic cancer, and cells lacking hENT1 expression are highly resistant to gemcitabine ( Mori et al, 2007 ; Perez-Torras et al, 2008 , 2013 ). There is increasing evidence supporting the view that hENT1 is a predictive biomarker for the use of gemcitabine.…”
Section: Transporters As Biomarkersmentioning
confidence: 99%
“…However, the evidence of hCNT1 loss during oncogenesis needs further investigation, because almost all the studies performed so far focused exclusively on hCNT1-related mRNA levels. We have recently demonstrated that restoration of hCNT1 function in pancreatic adenocarcinoma cell lines is able to induce cell cycle arrest, increase cell death by a non-apoptotic mechanism, trigger changes in some intracellular signaling cascades and inhibit cell migration ( Perez-Torras et al, 2013 ). More importantly, all these events can also be induced when expressing a mutated hCNT1 protein that localizes to the plasma membrane but lacks the ability to translocate substrates.…”
Section: Nts As Drug Targetsmentioning
confidence: 99%
“…These results can also have an impact on basic scientific research. Since some transporter subtypes show significant changes in expression levels between normal and pathological conditions (i.e., cancer), and these changes in transporter expression are usually important for the pathological conditions to persist, a fluorescent compound that is subtype-specific (e.g., pyrrolo-gemcitabine) for a certain transporter family can be a valuable tool to study the role of transporter subtypes in human health and disease through live cell imaging (Farre et al, 2004;Zhang et al, 2006;Bhutia et al, 2011;Perez-Torras et al, 2013). Taken together, this work not only represents an structural study of substrate and drug selectivity by membrane transporters, but our results also provide proof of principle for using this type of structure-function study for modifying drugs so that they are recognized and taken up into the cell by their cognate transporters more efficiently and selectively (Han and Amidon, 2000;Majumdar et al, 2004).…”
Section: Research Articlementioning
confidence: 99%